Employee experience and perceptions of an organizational road-safety intervention – A mixed-methods study. (February 2021) - Rispler, Clara; Luria, Gil
Highlights: Organizations with higher safety climate are perceived as a reliable source of safety promotion. Employee Intrinsic motivation helps predict OHS program participation. Desired safety behavior change in an OHS program is promoted by participant intrinsic motivation. Abstract: Phone use while driving is a common cause of road casualties. This study examines whether organizational influence can be leveraged to reduce employees' phone use at the wheel. It explores employees' views on a "no-phone-use-while-driving" road safety organizational intervention. Forty-five employees from six different organizations completed a four-month no-phone use-while-driving Organizational Health and Safety (OHS) intervention. Quantitative data on organizational safety climate and safety motivation were gathered through a survey, and a smartphone monitoring application provided objective data on the number of times the driver touched the phone screen while driving. Employees' experiences and perceptions of the intervention and its impact were measured qualitatively through interviews. Content analysis of the interview data provided insights into the impact of the intervention on participants, how the organization influenced the intervention, and where participants perceived the locus of control over their behavior (internally or externally). A mixed-methods analysis showed that employees who perceived the organizational safety climate as higher saw the workplace as a reliable means of promoting a safety program. Participants who frequently spoke in terms of an internal locus of control had higher safety motivation, and were more likely to reduce the degree to which they touched the screen while driving. Organizational safety climate and safety motivation have a positive role in predicting participation in a safety intervention within an organizational setting, and in promoting the desired behavior change. These findings can help organizations better manage their safety intervention programs and improve employees' safety performance.